2022
DOI: 10.1186/s12917-022-03243-2
|View full text |Cite
|
Sign up to set email alerts
|

Moniezia benedeni infection enhances neuromedin U (NMU) expression in sheep (Ovis aries) small intestine

Abstract: Background Neuromedin U (NMU) plays an important role in activating the group 2 innate lymphoid cells (ILC2s) and initiating the host’s anti-parasitic immune responses. It is aimed to explore the distribution characteristics of NMU in the sheep small intestine and the influence of Moniezia benedeni infection on them. In the present study, the pET-28a-NMU recombinant plasmids were constructed, and Escherichia coli. BL21 (DE3) were induced to express the recombinant protein. And then, the rabbit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…In this study, under the optimal IPTG concentration, as the induction time passed, the expression level of the TLR8 recombinant protein showed a trend of rst increasing and then gradually decreasing, and the recombinant protein was mainly expressed in the form of inclusion bodies. These results were basically consistent with the previous studies, in which polyclonal antibodies were prepared by prokaryotic expression [30,39]. The reason for this might be that the growth and reproduction of the bacterial population need to go through the lag phase, logarithmic phase, stationary phase and decline phase [40].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, under the optimal IPTG concentration, as the induction time passed, the expression level of the TLR8 recombinant protein showed a trend of rst increasing and then gradually decreasing, and the recombinant protein was mainly expressed in the form of inclusion bodies. These results were basically consistent with the previous studies, in which polyclonal antibodies were prepared by prokaryotic expression [30,39]. The reason for this might be that the growth and reproduction of the bacterial population need to go through the lag phase, logarithmic phase, stationary phase and decline phase [40].…”
Section: Discussionsupporting
confidence: 92%
“…The spatial distribution of SNAP-25 in sheep's small intestines was observed under a fluorescent microscope and images were acquired (The DV Elite™ Imaging System, GE, USA). (DAPI: UV excitation wavelength 330–380 nm, emission 420 nm, blue; FITC: excitation 465–495 nm, emission 515–555 nm, green) [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is prevalent worldwide, mostly endemic, and it is also an important pathogen of sheep tapeworm disease. Our previous research showed that M. benedeni infection can substantially reduce the densities of IgA + , IgG + , and IgM + cells in the sheep's intestine [ 30 ], and markedly enhance the density of intestinal IgE + cells [ 51 ] and CD3 + T cells [ 53 ] as well as the expression of NMU [ 31 ].However, at present, there are few reports regarding the impact of M. benedeni infection on the expression of SNAP-25 in the sheep's intestine. In this study, the prokaryotic gene expression of SNAP-25 in sheep was investigated, the rabbit anti-sheep SNAP-25 polyclonal antibodies were prepared, and the expression and distribution patterns of SNAP-25 in the sheep's intestine both before and after M. benedeni infection were analyzed.…”
Section: Introductionmentioning
confidence: 99%